Sustainable development and indicators : information of ecological, economical, social and regional activity in rural areas - Luostarinen, Matti (Maa- ja elintarviketalouden tutkimuskeskus, 2001)
Environmental problems, partly due to agriculture, are among the most serious issues in the EU counties. BSE is only one of the big problems in the food staff chain of global marketing. Environmental questions concerning agriculture are complicated and closely related to many other issues, e.g. the food global markets and the well-being of the population, etc. Therefore, it is difficult to find effective solutions in political level. Indicators are a way for operationalisation of the sustainability. Agri-environmental indicators are used for identifying the key processes and changes in relationships between agriculture and environment. Currently development of these methods in one of the topics in international discussions, because there is an urgent need to get reliable information for supporting the political decision making and for assessing the effects of political measures. Work is done, in many international organisations among them OECD, United Nations and EuroStat, to develop the indicators. Also at a national level there is e great emphasis for defining methods for measuring agricultural impacts on environment. In Finland this work is actively done in the Ministry of Agriculture and in the Ministry of Environment together with Agricultural Research Centre of Finland. The aim of the SUSAGRI-project has been to develop instruments like indicators and evaluation methods, and promote practical solutions for sustainable agriculture. The Finnish Agri-Environmental program is a case study for identifying important processes of agricultural sustainability. The analysing subtasks have been I) socio-economic, II) regional and demographic, III) economical, IV) landscape, V) administration and practical subtasks in the river-Loimijoki-area and building Agro Park to demonstrate sustainable landscape-, nature- and cultivation practices to both local farmers and inhabitants as well as to the researchers and large public.
Keywords: Ys; Suomi; ympäristö; indikaattori; maisema; kestävyys; Finland; environment; indicators; agriculture; landscape; sustainability; interdisciplinary